Nuclear factor (NF)-κB-dependent thyroid hormone receptor β 1 expression controls dendritic cell function via Akt signaling - Mascanfroni, I.D. (2010)
Despite considerable progress in our understanding of the interplay between immune and endocrine systems, the role of thyroid hormones and their receptors in the control of adaptive immunity is still uncertain. Here, we investigated the role of thyroid hormone receptor (TR) β 1 signaling in modulating dendritic cell (DC) physiology and the intracellular mechanisms underlying these immunoregulatory effects. Exposure of DCs to triiodothyronine (T 3 ) resulted in a rapid and sustained increase in Akt phosphorylation independently of phosphatidylinositol 3-kinase activation, which was essential for supporting T 3 -induced DC maturation and interleukin (IL)-12 production. This effect was dependent on intact TRβ 1 signaling as small interfering RNA-mediated silencing of TRβ 1 expression prevented T 3 -induced DC maturation and IL-12 secretion as well as Akt activation and IκB-ε degradation. In turn, T 3 up-regulated TRβ 1 expression through mechanisms involving NF-κB, suggesting an autocrine regulatory loop to control hormone-dependent TRβ 1 signaling. These findings were confirmed by chromatin immunoprecipitation analysis, which disclosed a new functional NF-κB consensus site in the promoter region of the TRB1 gene. Thus, a T 3 -induced NF-κB-dependent mechanism controls TRβ 1 expression, which in turn signals DCs to promote maturation and function via an Akt-dependent but PI3K-independent pathway. These results underscore a novel unrecognized target that regulates DC maturation and function with critical implications in immunopathology at the crossroads of the immune-endocrine circuits. © 2010 by The American Society for Biochemistry and Molecular Biology, Inc.